2018
DOI: 10.3928/23258160-20180628-08
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Idiopathic Choroidal Neovascularization Using Fluorescein Angiography, Indocyanine Green Angiography, and Optical Coherence Tomography Angiography

Abstract: OCTA is a useful, noninvasive tool to detect, characterize, and follow-up on cases of suspected iCNV with utility comparable to or even better than traditional angiography techniques. [Ophthalmic Surg Lasers Imaging Retina. 2018;49:516-522.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Follow up OCTA after 4 weeks revealed marked resolution (network of individual vessels not identifiable with >50% reduction in size of visible membrane; grading of resolution proposed by authors. 3 Patient maintained visual acuity with resolution of subjective symptoms.…”
Section: Case Series 1 -'Simplifying Diagnosis'mentioning
confidence: 88%
“…Follow up OCTA after 4 weeks revealed marked resolution (network of individual vessels not identifiable with >50% reduction in size of visible membrane; grading of resolution proposed by authors. 3 Patient maintained visual acuity with resolution of subjective symptoms.…”
Section: Case Series 1 -'Simplifying Diagnosis'mentioning
confidence: 88%
“…It has been observed that the OCT-angiographic appearance of iCNV networks is different from neovascular AMD membranes. The neovascular network in iCNV is usually composed of well-defined compact lesions with internal anastomosing capillaries,[ 9 15 ] whereas in AMD-associated CNV, the network is identified as a central feeder trunk with vessels radiating out in a branching pattern. [ 16 ] The difference could also be ascribed to the fact that AMD is more commonly associated with type 1 CNV,[ 17 ] whereas all our cases were type 2 CNV.…”
Section: Discussionmentioning
confidence: 99%
“…Arborizing morphology was identified as multiple dendritic, branching vessels, not limited within the perimeter of the network [ Figure 1 ]. [ 9 ] To minimize errors occurring due to automated segmentation of OCT-A, manual segmentation of all OCT-A acquisitions was done. The segmentation level of follow-up imaging was matched to the pretreatment images.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early stage of CNV, there are usually no conscious symptoms ( Aggarwal et al, 2019 ). With the development of the disease, it can cause visual impairment, visual distortion or central dark spot ( Kumar et al, 2018 ). In general fundus examination, the manifestation is subretinal hemorrhage and lipid-like exudation.…”
Section: Introductionmentioning
confidence: 99%